Joint attention performance in preschool-aged boys with autism or fragile X syndrome - Thurman, Angela John; Dimachkie Nunnally, Amanda (Frontiers in Psychology, 2022)
Early development marks a period of rapid learning facilitated by children’s natural curiosity about the people around them. In children with typical development, these early social attentional preferences set the foundation for learning about and from the surrounding world of people. Much of this learning happens using joint attention, the ability to coordinate attention between people and objects of mutual interest. It is well documented that decreased gaze use is commonly observed in individuals with autism and individuals with fragile X syndrome (FXS). Despite the growing body of research comparing phenotypic similarities between individuals with autism and individuals with FXS, no studies have directly compared joint attention performance between these groups. In the present study, we considered the similarities and differences in joint attention between preschool-aged boys with autism or FXS, and the relation between joint attention, language, and other phenotypic characteristics known to differ between boys with autism and boys with FXS. Although joint attention appeared similar, between-group differences emerged when controlling for the influence of age, nonverbal IQ, and autism symptom severity. Differences were also observed when considering how joint attention performance related to other aspects of the phenotype. For example, the association between joint attention and language performance was significantly stronger in boys with autism than boys with FXS, even after controlling for nonverbal IQ. In contrast, the association between joint attention and anxiety symptom severity was significantly stronger in boys with FXS than in autism. These data offer a start to a deeper understanding of the similarities and differences between the autism and FXS phenotypes.